129k views
1 vote
Hey can you please help me posted picture of question :)

Hey can you please help me posted picture of question :)-example-1

2 Answers

5 votes
The solutions for the equation are A and c
User Rluks
by
6.1k points
1 vote
Answer:
The roots are 3 and -6

Step-by-step explanation:
The general formula of the quadratic equation is:
ax²+ bx + c = 0
The given equation is:
x² + 3x - 18 = 0
By comparison, we can find that:
a = 1
b = 3
c = -18

To get the roots, we will use the quadratic formula shown in the attached image.

By substituting in the equation, we would find that:
either x =
(-3 + √((3)^2-4(1)(-18)) )/(2(1)) = 3

or x =
(-3 - √((3)^2-4(1)(-18)) )/(2(1)) = -6

This means that the roots are: 3 and -6

Hope this helps :)
Hey can you please help me posted picture of question :)-example-1
User Iamchoosinganame
by
6.2k points